Banksy : you are an acceptable level of threat and if you were not you would know about it - Shove, Gary; Potter, Patrick; Banksy (Great Britain : Carpet Bombing Culture, 2014)
This title collects the works of one of the most succesful and well-known street artists ever, Banksy.
Previous edition: 2012.
Keywords: Banksy; Street art -- Great Britain -- Pictorial works; Graffiti -- Great Britain -- Pictorial works